Efektifitas Pengembangan Collaborative Learning Management System (CLMS) Untuk Meningkatkan Keterlibatan Belajar Mahasiswa - Ns., M.Med.Ed., Suryani; Sulistyaningsih; Sadr Lutfi Mufreni; Farida Noor Rohmah (Infomasi dan Promosi Kesehatan, 2024)
Student involvement in the learning process is crucial as it affects their learning success. The implementation of online learning at UNISA Yogyakarta faced obstacles due to low student participation. Student interest in accessing the LMS is influenced by the quality of the LMS. The results of LMS monitoring and evaluation over the past year showed an average score of 2.28 (categorized as sufficient). Courses with good LMS evaluation scores accounted for 23.6%. The development of the LMS is an effort to increase student involvement in cognitive, behavioral, emotional, and performance aspects. This research is a collaborative study on LMS development in partnership with Universiti Malaysia Pahang. The development method uses the 4D model (Define, Design, Develop, Disseminate). The measurement of learning engagement, as the impact of CLMS development, was conducted using the Online Student Engagement Scale (OSE) adapted from Dixson (2015). Data analysis employed qualitative analysis and statistical frequency distribution for each engagement component. The results showed that the average engagement of respondents at UNISA Yogyakarta before CLMS development was 74.7, and the post-test average was 78.8, indicating a score increase of 5% (4.1). Meanwhile, the average engagement score of respondents at UMP was 73.4. The effectiveness test resulted in a p-value of 0.002 (p<0.05), indicating that CLMS development is effective in improving student learning engagement. Each course is expected to develop innovative teaching media within the LMS to enhance the student learning process.